INTEGRATED MODEL FOR REPUTATION EVALUATION BASED ON REPTRAK AND AMEC - Shuranov, Mykhaylo; Hrynyshak, Tetiana (Current Problems of Sustainable Development, 2026)
The article addresses the problem of evaluating corporate reputation in the context of digital transformation. It is determined that traditional approaches to communication evaluation are largely focused on quantitative indicators, such as media outputs, reach, and frequency, which limits their ability to capture actual changes in stakeholder perceptions and behavior. This creates a gap between operational communication metrics and strategic management outcomes. In this regard, the study substantiates the need for an integrated approach that allows linking communication activities with reputational changes and organizational performance. The purpose of the research is to develop an integrated model for reputation evaluation based on the combination of the RepTrak methodology and the AMEC Integrated Evaluation Framework. The proposed model includes three interconnected levels: operational, tactical, and strategic. The operational level focuses on monitoring communication activities and information signals, including their volume, tone, and distribution channels. The tactical level is aimed at assessing changes in stakeholder perceptions using reputation drivers and emotional indicators. The strategic level evaluates how these perception changes are transformed into behavioral and economic outcomes, such as trust, recommendation, investment intentions, and support for the organization. The model provides a structured approach to identifying causal relationships between communication processes, perception dynamics, and organizational results. The practical significance of the research lies in the possibility of applying the proposed model to improve reputation management systems, enhance analytical capabilities, and support evidence-based decision making in digital environments characterized by uncertainty, high information intensity, and the rapid spread of both reliable and manipulative content. The implementation of this approach contributes to bridging the gap between communication measurement and strategic management, ensuring a more comprehensive and effective evaluation of corporate reputation.